Physical and Mechanical Properties of Rattan and Polylactic Acid Biocomposites Printed Using Fused Filament Fabrication - Sánchez-Cruz, Martha Lissette; Morales-Martin, Luz Yolanda; Capote Rodríguez, Gil (Ingeniería, 2025)
Context: The use of alternative materials in construction requires the implementation of new methods that allow addressing the problems associated with the manufacture of traditional composite materials. In recent years, additive manufacturing techniques have attracted the attention of entrepreneurs and researchers due to its ease in processing complex designs and its low processing times. However, there is little information about the mechanical performance of composites obtained from the processing of biopolymer filaments reinforced with plant fibers. Method: We evaluated the mechanical behavior of 3D-printed biocomposites subjected to axial tension loads. For the experimental design, filaments were constructed using 90% polylactic acid granules and 10% pulverized rattan fibers. The properties of the filaments were analyzed through microscopy, density, thermogravimetry, roughness, and hardness tests. The specimens were printed according to the dimensions specified in ASTM D638, and the effect of infill density and printing orientation on their physical and mechanical properties was analyzed. A statistical analysis was carried out in order to formulate equations allow predicting the behavior of the material based on the printing parameters considered. Results: The obtained filaments were characterized and compared against their unreinforced counterparts. The specimens were printed using the fused deposition method. The effect of the printing parameters on the physical and mechanical properties of the stressed biocomposite was determined, and the impact of the studied variables was analyzed using a central composite design. Conclusions: The surface roughness of the samples increased with the printing orientation and decreased as the infill density increased. Hardness and tensile strength increased significantly with increasing infill density, and they decreased with an increasing printing angle. The probes printed with 80% infill showed a notable increase in rigidity.